Laser-induced Breakdown Spectroscopy (LIBS) as a diagnostics tool for biological tissue analysis - Mehari, Fanuel (FAU University Press, 2025)
In this thesis, the emerging analytical technique laser‐induced breakdown spectroscopy(LIBS) is investigated as a diagnostic tool for biological tissues analysis. The two main objectives of the work are using LIBS to provide tissue type feedback information during laser surgery and to use LIBS as an imaging modality by mapping the distribution of elements in tissues. The viability of LIBS for the direct measurement of elements in biological tissue and indirect measurement of molecules has been presented. The applicability of LIBS for real‐time tissue classification to use it as a feedback control mechanism of clinical laser surgery systems has been demonstrated. High classification accuracy of different tissues has been achieved. The results of measuring the distribution of elements in tissues shows that LIBS can be a powerful imaging modality for medical applications that seek to understand the chemical microenvironment of tissues. This has been demonstrated by mapping the different distribution of certain elements between cancerous and healthy tissues.